The Role of Company Size as a Moderator in the Relationship of Governance, Green Financing, and Profitability to Sustainability Reporting Disclosure in the Financial Sector - Lestari, Laely Puji; Nugroho, Lucky (Baca Dulu Publisher, 2025)
Growing pressures from stakeholders for transparency is driving the need for financial sector firms to enhance the Sustainability Reporting Disclosure (SRD). Although differences in disclosure continue to coexist within the context of identical regulation, this issue implies some research questions and gaps: what are the determinants of these differences in the two countries? This is the premise upon which this work seeks to explore the impact of board size, gender diversity, Green Financing, and Return on Assets (ROA) on SRD, and the moderation effect of company size. Applying quantitative method, this research analyses secondary data collected from financial sector companies which were listed in the BEI during 2019–2023. The direct and interaction effects are estimated using moderation regression. The results indicated that board size, gender diversity, and Green Financing have significant positive influence on SRD, however, ROA to SRD is positive but insignificant. Finally, firm size moderated the effect of board size, gender diversity, and Green Financing on SRD, while it did not moderate the effect of ROA and SRD. The results of this study support the stakeholder theory that environmental governance and performance are expected to improve the quality of sustainability disclosure in organization when scaled up. The originality of the paper lies in the simultaneous combination with respect to controls, Green Financing, profitability and the moderation of company size in the distinctive context of regulated industries.